Beyond the Theory of Planned Behavior: Evidence from Whistleblowing Research in Accounting Theory - Meita Larasati; Zakiyah Sharif; Al Jaffri Saad; Ummu Salma Al Azizah (Jurnal Akuntansi dan Bisnis, 2026)
This article aims to present a comprehensive and systematic evaluation of the Extended Theory of Planned Behavior (ETPB) by mapping its core research areas over the past decade and proposing a structured thematic classification and future research agenda. Using a systematic literature review and thematic analysis of Scopus indexed 202 articles between 2015 and 2025 by Watase, this study develops an integrative multidimensional framework incorporating antecedents, outcomes, and contextual contingencies relevant to ETPB. The results reveal major trends in publication patterns, research themes, and journal outlets, while identifying key theoretical, methodological and contextual gaps that suggest clear directions for future research. The findings indicate that moral norm has emerged as the most dominant extension variable, highlighting the growing importance of ethical and value-based considerations in behavioral intention research. Furthermore, whistleblowing has become one of the most prominent applications of ETPB, demonstrating the relevance of moral, organizational, professional, and contextual factors in explaining ethical decision-making. Overall, although the Extended Theory of Planned Behavior enhances behavioral explanation by incorporating moral and contextual factors, its increasing complexity and limited methodological diversity indicate the need for clearer theory, stronger research designs, and wider validation. Keyword: Extended Theory of Planned Behavior, Systematic Literature Review, Watase, Thematic Analysis, Conceptual Framework Development